About improvement of work against terrorism and extremism in Kazakhstan (Journal of actual problems of jurisprudence, 2018)
This article analyzes the actual threats of terrorism and religious extremism in Kazakhstan. Underlines factors which have influence on the growth of the existing problem in the country. In order to determine the sources of vulnerabilities and gaps in anti-extremist and anti-terrorist activities of the state made a brief analysis of the characteristics and prerequisites of terrorist attacks carried out in Aktobe and Almaty, respectively, in June and July of 2016. The issues of penitentiary prevention of religious extremism and extremist crimes prerequisites relapse due to the presence of conditions for concealment carriers radicalized their true beliefs, and sometimes inefficient provision of correctional impact on the convicts. The article presents the author’s arguments about force and preventive approaches to combating religious extremism and terrorism, as well as a preference for preventive work in this direction. On the basis of the research author propose a number of conclusions and suggestions.Key words: terrorism, religious extremism, terrorist attacks, radical, preventive.